2009
DOI: 10.1063/1.3120566
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced exciton diffusion in an organic photovoltaic cell by energy transfer using a phosphorescent sensitizer

Abstract: We demonstrate enhanced exciton diffusion in an organic photovoltaic cell through the incorporation of a phosphorescent sensitizer. The increase in exciton diffusion length (LD) is realized using a composite electron donor layer consisting of a N,N′-bis(naphthalen-1-yl)-N,N′-bis(phenyl)-benzidine (NPD) host doped with the phosphorescent guest fac-tris(2-phenylpyridine) iridium [Ir(ppy)3]. The presence of the phosphor at low concentration allows for the population of the long-lived NPD triplet state and an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 22 publications
2
92
0
Order By: Relevance
“…Doping of a BHJ with nanoparticles can increase the effective exciton lifetime and thus improve the power conversion efficiency [24,25,65,66]. Furthermore, in phosphorescent OLEDs, organometallic complexes are used to improve the efficiency.…”
Section: Phosphorescent Dopantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doping of a BHJ with nanoparticles can increase the effective exciton lifetime and thus improve the power conversion efficiency [24,25,65,66]. Furthermore, in phosphorescent OLEDs, organometallic complexes are used to improve the efficiency.…”
Section: Phosphorescent Dopantsmentioning
confidence: 99%
“…Most kMC models either account for singlet [10,[17][18][19] or triplet exciton dynamics [20][21][22][23] for the use in OSCs or OLEDs, respectively. However, the interplay between singlets and triplets can be used to modify exciton lifetimes and diffusion lengths, which is a promising way to tailor efficiencies in organic devices and therefore requires a better understanding [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the strong intersystem-crossing mechanism that take place in these complexes have been exploited to design organic solar cells (OSCs) of improved power conversion efficiency [3,4]. In fact, in organic heterojunctions, sensitizing transition-metal complexes are utilized as promoters in converting photogenerated singlet excitons into long-lived triplet excitons, thereby increasing the probability for an exciton to diffuse to a donor-acceptor interface and dissociate into collectible charges [3,4].…”
Section: For a Review)mentioning
confidence: 99%
“…In fact, in organic heterojunctions, sensitizing transition-metal complexes are utilized as promoters in converting photogenerated singlet excitons into long-lived triplet excitons, thereby increasing the probability for an exciton to diffuse to a donor-acceptor interface and dissociate into collectible charges [3,4]. In a recent study [3] it was reported that incorporating Ir(ppy) 3 (in concentrations as low as few mass percents) into electron-donating polymers nearly doubled the photovoltaic efficiency of the considered organic heterojunctions.…”
Section: For a Review)mentioning
confidence: 99%
See 1 more Smart Citation